P-96 A snapshot of social deprivation and multi-morbidity in a hospice inpatient population. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Neal, Abigail; O'Riordan, Maire; Spenceley, Julie; Hoy, Paul; Carduff, Emma
Abstract : Introduction: Recent research has suggested that people living with long-term illnesses in socially deprived areas have poor access to specialist palliative care services and poor overall quality of care in the last three months of life. Aim: To describe the inpatient population of a hospice ward and to explore the relationship between level of deprivation and the prevalence of co-morbidities. Methods: Data were collected from patient notes, nursing documentation and computer systems for 30 patients (total number of beds) over 1 week. Scottish Index of Multiple Deprivation quintiles (SIMD 1 – most deprived; SIMD 5 – least deprived) were assigned to assess level of deprivation based on patient postcode. Data were analysed using t-test on Graphpad PRISM. Findings: The sample comprised of 15 female and 15 male patients ranging in age from 56–88 years. Eighteen had been admitted from home, 11 from hospital and one from the hospice outpatient clinic. Primary disease was more commonly malignant than non-malignant (26:4 respectively). Fourteen were from SIMD quintile 1 (most deprived), but only two were from SIMD 5 (least deprived). Patients from areas of high deprivation had nearly double the number of admissions to hospital in the preceding 12 months (SIMD 1–2 mean 3.7 (95% CI: 2.4–5.1); SIMD 3 and above 2.1 (1.4–2.7) P = 0.02). The number of co-morbidities ranged from a single disease to nine; there was no correlation with SIMD quintile. Conclusion: The patients captured in this study were predominately from more deprived areas, which reflects the local population. Importantly, these patients had significantly more admissions to hospital compared with patients from less deprived areas. More research is required to understand the reasons for this, including the extent to which these admissions are occurring out of hours, and to determine the level of need for patients and families living and dying in deprived areas.